Coastal resource management (CRM) of Miag-ao assessment of Municipal Local Government Unit's (LGU's) performance. - Indig, Alvin Rey G. (University of the Philippines, College of Arts and Sciences, Division of Social Sciences, 2008)
The study sought to assess the Municipality of Miag-ao's performance in CRM. Key informants from seven coastal barangays of Miag-ao, Iloilo were considered in the study. Secondary data analysis, surveys and interviews were used in gathering data from January 2008 to mid-February of the same year. Results showed that CRM system of Miag-ao is controlled and dominated by the chairpersons of the barangay's Fisheries and Aquatic Management Council (BFARMC). The assessment of the different CRM phases obtained relatively low assessment ratings from the key informants of the seven barangays ; while the municipal LGU gave itself relatively high assessment ratings. This study analyzes the reasons behind the discrepancy of the research participants perceptions of the CRM performance of the local government of Miag-ao. Fiscal, socio-cultural, administrative and governance constraints are identified as some of the key areas that needed to be addressed to improve CRM in Miag-ao.